Engendering Gendered Knowledge: Assessing the Academic Appropriation of Hegemonic Masculinity - Messerschmidt, James W. (Men and masculinities, 2012)
The appropriation of concepts long established as salient contributions to gender theory and research recently has come under scholarly scrutiny. In this article, the author contributes to this dissection of crucial gender concepts by assessing the recent academic appropriation of the reformulated concept of “hegemonic masculinity” and how this appropriation engenders gendered knowledge. The author first briefly revisits the concept of hegemonic masculinity as reformulated by Connell and Messerschmidt. Following this, the author examines selected studies to illustrate how hegemonic masculinity has been appropriated differently, how this dissimilarity is significant for the production of gendered knowledge, and how several new directions in the appropriations extend gendered knowledge on hegemonic masculinity. Finally, the author discusses the relevance of all his conclusions to the wider debates over the concept of hegemonic masculinity and posits how these conclusions arguably impact future feminist/gender research and theory construction.